Quality of Life Following Epilepsy Surgery - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
A prospective study of the families of 35 children with intractable epilepsy who underwent epilepsy surgery at Sydney Children's Hospital, NSW, Australia, found that those who were seizure-free had a greater improvement in the quality of life (QOL) than children with persistent seizures.